Սյունյաց գահակալ իշխանների Արևիքի ճյուղը - Մանուչարյան, Աշոտ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
ՀՀ Սյունիքի մարզի Մեղրու տարածաշրջանում վիմագրագիտական հավաքչական գործունեության, շրջագայությունների ընթացքում ընդօրինակված արձանագրությունների շարքում առանձնանում են X դարի առաջին կեսի չորս խաչքարային հիշատակագրություններ, որոնցում, ըստ էության, հիշատակվում են Սյունյաց լեռնաշխարհի պատմական Արևիք գավառի գահակալ իշխաններ: Նրանց մասին պատմագիրները լռում են: В результате проведенных исследований к пяти ветвям правящих престольных князей Сюника нами была добавлена шестая – ветвь князей провинции Аревик. Основанием для этого послужила надпись на хачкаре, установленном в южном углу восточной стены церкви Св. Степаноса в селе Мегри Ванк, отреставрированной в 1554 году. В этой надписи, датированной 902 годом, упоминается «Владыка Смбат». In the result of the conducted research, we added the sixth branch to the five ones of the ruling royal princes of Syunik – branch of princes of the province of Arevik. The basis for this was the inscription on the khachkar installed in the southern corner of the eastern wall of the Church of St. Stepanos in the village of Vank restored in 1554, Meghri region. This inscription, dated 902, mentions “Lord Smbat”. According to the research and purchase contracts of the Tatev Monastery for the period from 839 to 891, the title of “Lord” was borne by diocesan bishops and throne princes. The same Smbat is mentioned on the khachkar, dated 911, which was erected in the rural area of Lichkvaz in the region of Meghri.
Keywords: Հնագիտություն